Properties of solutions to a second order nonlinear differential equation - Allan J. Kroopnick (International Journal of Mathematics and Mathematical Sciences)
In this note, we show when all solutions to the nonlinear differential equation x″+c(t)f(x)g(x′)x′+a(t,x)=0 are bounded. Furthermore, the solutions are either oscillatory or monotonic and asymptotically stable.